Faktor Faktor yang Mempengaruhi Partisipasi Politik Pemilihan Legislatif di Kecamatan Dimembe Kabupaten Minahasa Utara - Supriati, Arie (Jurnal Aplikasi Manajemen, 2014)
This study aims to determine the factors that influence political participation in the legislative elections Dimembe District of North Minahasa regency. The method used is descriptive survey. purposive sample using Product Moment correlation analysis research hypothesis that factors affecting Political Participation legislative election in the District of North Minahasa Regency Dimembe r r xy or count is 0, compared with 744 r on the importance of table 1% 0,380 and 5% significance of the result is calculated 0.744 0.294 r > 0.380 and 0.294 (Regreater of the table) means that the hypothesis is accepted. The factors that influence the Legislative Elections Political Participation in the District of North Minahasa regency Demembe is 55% determined by political socialization, political attitudes and political communication, and 45% is determined by other factors not examined. Legislative Elections Political participation is the people who choose a political party or political office, membership of political organizations to fight for the program through the legislative elections, political socialization, political attitudes and political communication.